Queuing up for justice: Elections and case backlogs - Siddhartha Bandyopadhyay; Bryan McCannon (University of Birmingham, Birmingham Business School, 2014)
We analyze the impact of prosecutor elections on case backlogs. Previous evidence has shown that re-election pressures result in more cases going to trial. Since trials require time and resources, one can expect an effect on the queue. Two competing theories are developed: one of signaling quality in an asymmetric information environment and one of effort exertion, each of which can explain increased trials before election, but differ in their predictions regarding the impact on backlogs. A district-level, panel data set of caseload flows in North Carolina is analyzed. Evidence is presented that contested re-elections are associated with a decrease in the number of cases handled and an acceleration of the growth of the backlog. This suggests that retention concerns lead to signaling which causes distortions, re-allocating resources from disposing cases to prosecuting cases at trial.
Keywords: K41; D82; 330; case backlog; elections; prosecutor